Understanding the Indian Consumer’s Attitudes with Respect to Clean Beauty - Tulsiani, Rimpie (Digital Repository of Theses, 2025)
“Clean beauty” – a fairly new word which encompasses a range of safe, natural and trustworthy ingredients and products. However, in India, the lack of a specific definition by regulatory organizations, allows consumers to create a definition of their own, and this is something brands as well do. The consumers of India continue to steer towards the natural and herbal narrative and hence clean beauty is considered synonymous to “organic”, “sustainable” or “healthy”. Many past literatures and studies on this topic have showed an absence of knowledge of the terms associated with clean beauty and therefore revealed the lack of cognizance of it. With the rising desire for transparency, consumers look for authentic information from sources they can trust. With the rising levels of e-commerce through the online channels of beauty and personal care products, it gives consumers a wider platform to research information and a wider reach to sources to know about the constituent ingredients. Generally, a known perception, which is also quoted in the paper, is that these green goods attract a greater purchase rate, acting as a deterrent to adopting clean beauty products. The aim of the research is to apprehend the Indian consumer’s awareness levels of clean beauty products, purchasing behavior of consumers vis-à-vis clean beauty products, the sensitivity of pricing strategies of green products, channels of information for clean beauty products and the consumers’ psychographic clusters and their purchasing behavior. The analyzed data has been received from Mintel Ltd, and further interpretations have been made. The data was collected using a structured questionnaire across India on a sample of 3000 participants. Result of analysis shows awareness levels are low, safety is a priority and the consumer are price sensitive as well. But consumers are highly influenced by word of mouth and trusted sources of information.